Selective delivery of PLXDC1 small interfering RNA to endothelial cells for anti-angiogenesis tumor therapy using CD44-targeted chitosan nanoparticles for epithelial ovarian cancer - Ga Hee Kim; Ji Eun Won; Yeongseon Byeon; Min Gi Kim; Tae In Wi; Jae Myeong Lee; Yun-Yong Park; Jeong-Won Lee; Tae Heung Kang; In Duk Jung; Byung Cheol Shin; Hyung Jun Ahn; et al. (Taylor & Francis Group, 2018)
Angiogenesis plays an essential role in the growth and metastasis of tumor cells, and the modulation of angiogenesis can be an effective approach for cancer therapy. We focused on silencing the angiogenic gene PLXDC1 as an important factor for anti-angiogenesis tumor therapy. Herein, we developed PLXDC1 small interfering siRNA (siRNA)-incorporated chitosan nanoparticle (CH-NP/siRNA) coated with hyaluronic acid (HA) to target the CD44 receptor on tumor endothelial cells. This study aimed to improve targeted delivery and enhance therapeutic efficacy for tumor anti-angiogenesis. The HA-CH-NP/siRNA was 200 ± 10 nm in size with a zeta potential of 26.4 mV. The loading efficiency of siRNA to the HA-CH-NP/siRNA was up to 60%. The selective binding of HA-CH-NP/siRNA to CD44-positive tumor endothelial cells increased by 2.1-fold compared with that of the CD44 nontargeted CH-NP/siRNA. PLXDC1 silencing by the HA-CH-NP/siRNA significantly inhibited tumor growth in A2780 tumor-bearing mice compared with that in the control group (p < .01), and mRNA expression of PLXDC1 was significantly reduced in the HA-CH-NP/siRNA-treated group. Furthermore, treatment with HA-CH-NP/siRNA resulted in significant inhibition of cell proliferation (p < .001), reduced microvessel density (p < .001), and increased cell apoptosis (p < .001). This study demonstrates that HA-CH-NP/siRNA is a highly selective delivery platform for siRNA, and has broad potential to be used in anti-angiogenesis tumor therapy.